Telemedicine for Outpatient Neurosurgical Oncology Care: Lessons Learned for the Future During the COVID-19 Pandemic - Daggubati, Lekhaj C. (World Neurosurg, 2020)
BACKGROUND: The coronavirus 2019 (COVD-19) pandemic has drastically disrupted the delivery of neurosurgical care, especially for the already at-risk neuro-oncology population. The sudden change to clinic visits has rapidly spurned the implementation of telemedicine. A recommendation care paradigm of neuro-oncologic patients limited by telemedicine has not been reported. METHODS: A summary of a multi-institution experience detailing the potential benefits, pitfalls, and the necessary considerations to outpatient care of neurosurgical oncology patients. RESULTS: There are limitations and advantages to incorporating telemedicine into the outpatient care of neuro-oncology patients. Telemedicine-specific considerations for each step and stakeholder of the appointment (physician, patient, scheduling, previsit, imaging, and physical examination) are examined. CONCLUSIONS: Telemedicine, pushed to prominence during this COVID-19 pandemic, is a powerful and possibly preferential tool for the future of outpatient neuro-oncologic care.